Selectivity of Rynaxypyr for three species of Phytoseiid mites relevant to coffee in Brazil - Reis, Paulo Rebelles; Franco, Renato André; Silva, Fábio M. Andrade (Coffee Science - ISSN 1984-3909, 2011)
Among the predaceous mites, those of the Phytoseiidae family are the most important and studied. The phytophagous mites Brevipalpus phoenicis (Geijskes, 1939) (Tenuipalpidae) and Oligonychus ilicis (McGregor, 1917) (Tetranychidae), on coffee trees (Coffea spp.), are frequently found in combination with the predaceous mites Iphiseiodes zuluagai Denmark & Muma, 1972, Amblyseius herbicolus (Chant, 1959) and Euseius citrifolius Denmark & Muma, 1970, among others. The purpose of this research was to study the effects of the insecticide rynaxypyr (chlorantraniliprole 200 SC) on these three species of Phytoseiidae, relevant to coffee and citrus, following standard laboratory procedures. Mated female mites were exposed to fresh-dried residues on a glass surface, with 7 treatments, 5 mites per glass plate and 6 replicates, in a completely randomized experimental design. Each test lasted 8 days, with a daily count of the surviving females and of eggs laid. Rynaxypyr, in all tested concentrations (15, 30, 50, 100 and 500 mg a.i./liter of water), was selective for the studied species, A. herbicolus, I. zuluagai, and E. citrifolius. Overall the treatments resulted in low mortality rates and negligible impact on the reproduction. Therefore, based on IOBC standards, rynaxypyr can be classified as not harmful (Class 1), comparable to the agrochemical hexythiazox equivalent to a harmless standard of selectivity in the laboratory. Rynaxypyr is therefore a complement to programs of integrated pest management, to preserve the populations of predatory mites in crops of coffee and citrus, among others, in Brazil.